A cashless society: benefits, risks, and issues ‐ Abstract of the London Discussion. (2018) - Unknown
Abstract : This abstract relates to the following paper: Achord, S., Chan, J., Collier, I., Nardani, S. and Rochemont, S. (2017). A cashless society: benefits, risks, issues (interim paper) . Institute and Faculty of Actuaries . Available at: http://www.actuaries.org.uk/documents/cashless-society-benefits-risks-and-issues